Exploring the Relationship between Masseter and Cervical Vestibular-Evoked Myogenic Potentials in Young Adults with Hearing Thresholds Less Than or Equal to 15 dB HL - Vispute, Rutuja; Neupane, Anuj Kumar (Journal of the American Academy of Audiology, 2023)
Background Cervical vestibular-evoked myogenic potentials (cVEMPs) and masseter vestibular-evoked myogenic potentials (mVEMPs) are considered to have a common saccular origin. While a few studies have examined both vestibular-evoked myogenic potentials (VEMPs) in individuals with brainstem disorders as part of a test battery, the relation between these two potentials has rarely been the subject of discussion.Purpose The present study explored the relation between mVEMPs and cVEMPs using electromyography (EMG)-scaled parameters in normal-hearing young adults.Research Design Within-subject study design.Study Sample Twenty young adults between 18 and 39 years of age (11 males, 9 females) participated in the study.Data Collection and Analysis cVEMP and mVEMP were performed on all the participants at 95 dBnHL with 500 Hz tone burst stimuli. Various VEMP parameters were evaluated including P13 and N23 peak latencies, the amplitude of the P13–N23 complex, and the Interaural Amplitude Asymmetry Ratio in EMG-scaled and unscaled conditions.Results All participants exhibited a 100% response rate for cVEMP and mVEMP responses. There were no significant ears and gender effect for both cVEMP and mVEMP. No correlation was found between cVEMP and mVEMP. There was no significant difference found between P1 and N1 latency values of cVEMP and mVEMP; however, a significant variation was observed for peak-to-peak amplitude both in EMG-scaled and unscaled conditions between cVEMP and mVEMP.Conclusions Minimal to no association between any parameters of cVEMPs and mVEMPs suggests no significant relationship between these two VEMPs.
Keywords: mVEMP; cVEMP; saccule; tone burst; masseter; trigeminal nerve